Synthesis and characterisation of divalent di(1, 3‐bis(diphenylphosphano)cyclopentadienyl)lanthanoid and alkaline earth complexes as potential platforms for heterometallic complexes. Issue 23 (7th October 2022) - Daniels, Daisy P.; Guo, Zhifang; Shephard, Angus C. G.; Deacon, Glen B.; Jaroschik, Florian; Junk, Peter C.
Abstract: New divalent lanthanoid and alkaline earth metal complexes bearing the 1, 3‐bis(diphenylphosphano)cyclopentadienyl ligand have been synthesised using the redox‐transmetallation protolysis (RTP) approach. From the reaction of the corresponding metal, diphenylmercury and the proligand C5 H4 (PPh2 )2, the compounds [M(η 5 ‐C5 H3 (PPh2 )2 ‐1, 3)2 (S)] (with M=Yb, S=(thf)2 or M=Yb, Eu, Ca, Sr, Ba, S=dme) were isolated and characterised by X‐ray diffraction and multinuclear NMR spectroscopy. These compounds may provide a platform for early‐late heterobimetallic complexes. Abstract :